DIGITALIZATION OF ECONOMICS AND DEVELOPMENT BANKS: PROSPECTS FOR EVALUATION ON THE EXAMPLES OF THE RUSSIAN FEDERATION AND VEB.RF - S. S. Matveevskii; N. N. Agafonova (Вестник университета)
The experience of using digitalization indexes to assess the digitalization level of the economy has been summarized: it is advisable to use interval indexes that allow us to divide countries into groups according to the digitalization level. Using the linear regression model developed by the authors has made it possible to establish a direct statistical relationship between the I-Desi digitalization index and per capita Gross Domestic Product for a number of developed and developing countries: more developed countries carry out digitalization faster. It has been concluded that the digitalization of the economy and the implementation of fintech are based on innovative methods of obtaining, processing and transmitting information, that allows you to use the digitalization index methodology for assessing the digitalization of economic processes in development banks, and new indexes are needed to assess the level of fintech implementation in development banks.